Early Education Innovation at Elementary School in Pandemic Covid 19 Era - Salmon Charles Siahaan; Florence Pribadi; Natalia Yuwono; Imam Santosa; Bella Meylani Lifindra; Azyvati Karensa Putera; Cassey Clarissa Gondo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The Grand Convalescene event was divided into handbook socialization and webinars with "Kesiapan Pendidikan Era New Normal" as the theme. The purpose of this event is to provide education, especially in the medical field, about preventing the spread of the COVID-19 and to prepare teachers and their staff to face the New Normal era. The method used in the community service activities was an online webinars, in the form of socialization and evaluation using questionnaire. The results of the analysis carried out using the questionnaire showed that by holding this event, participants became more aware of all forms of information that could help them understand COVID-19 prevention and preparation for the New Normal era. The conclusions of this activity were socialization activities provide benefits for the community and teachers in understanding the conditions in the New Normal era, then this activity helps the community and teachers to prepare themselves for facing the New Normal era, and finally helps the community and teachers in understand the prevention of COVID-19.